Understanding the Differences between England, Great Britain, and the United Kingdom - Budiani, Revalio; Rosnawati, Emy; Prasetyo, Suyo Gigih (Proceedings of The ICECRS, 2023)
This data article delves into delineating England, Great Britain, and the United Kingdom, emphasizing their distinctions. England, part of Great Britain, encompasses the largest island in the British Isles alongside Scotland and Wales. The UK, as a sovereign state, incorporates England, Scotland, Wales, and Northern Ireland. Utilizing historical context, the article sheds light on the formation of these entities and addresses pertinent contemporary political and social issues. Recognizing these nuances holds crucial implications for fostering global relations and facilitating international collaboration.Highlights : Clarifying England, Great Britain, and the UK distinctions Historical formation and current socio-political issues Significance for global relations and international cooperation Keywords: England, Great Britain, United Kingdom, history, political issues.